1988
DOI: 10.1111/j.1399-6576.1988.tb02771.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rectal to intramuscular administration of midazolam and atropine for premedication of children

Abstract: The effectiveness of midazolam and atropine as anaesthetic premedication was investigated, comparing rectal to intramuscular administration. A total of 202 children varying in age from 10 months to 9 years, who had been admitted to the Day Surgery Department for short ENT procedures, were assigned to one of two groups on a random basis. The first group (n = 102) was given 0.5 mg/kg midazolam and 0.05 mg/kg atropine as a rectal solution 30 to 75 min prior to induction, while the second group (n = 100) was given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 6 publications
0
18
0
1
Order By: Relevance
“…Drugs currently used in clinical practice are reported in the following studies: midazolam was investigated in 33 trials [7, 1416, 19, 27, 28, 31, 33, 35, 39–45, 47, 48, 5054, 59, 61, 63, 66–71], nitrous oxide in seven [26, 30, 34, 42, 46, 50, 51], ketamine in eight [13–17, 26, 34, 37, 44, 49, 70], dexmedetomidine in one [49] and propofol in four [13, 14, 46, 47]. Besides, all drugs investigated in 23 studies were the ones currently used: 19 involved midazolam [7, 19, 27, 31, 33, 35, 40, 41, 5052, 54, 61, 63, 66–70], three nitrous oxide [46, 50, 51], four ketamine [13, 17, 49, 70], one dexmedetomidine [49] and two propofol [13,46]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs currently used in clinical practice are reported in the following studies: midazolam was investigated in 33 trials [7, 1416, 19, 27, 28, 31, 33, 35, 39–45, 47, 48, 5054, 59, 61, 63, 66–71], nitrous oxide in seven [26, 30, 34, 42, 46, 50, 51], ketamine in eight [13–17, 26, 34, 37, 44, 49, 70], dexmedetomidine in one [49] and propofol in four [13, 14, 46, 47]. Besides, all drugs investigated in 23 studies were the ones currently used: 19 involved midazolam [7, 19, 27, 31, 33, 35, 40, 41, 5052, 54, 61, 63, 66–70], three nitrous oxide [46, 50, 51], four ketamine [13, 17, 49, 70], one dexmedetomidine [49] and two propofol [13,46]. …”
Section: Resultsmentioning
confidence: 99%
“…Anterograde amnesia was evaluated in all studies, whereas retrograde amnesia was assessed in only 10 studies [7,33,35,37,39,40,52,54,60,66]. Amnesia was evaluated mainly by measuring patient recall of pictures/toys and events, except for the six trials [13,41,16,19,38,42].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, laboratory research has consistently shown that benzodiazepines produce anterograde amnesia-impaired memory for information learned after drug administration with no impairment for information learned pre-drug (Curran 1986). The present study was designed to extend prior lab-based findings to an applied setting where such amnestic effects might be beneficial (DeJong and Verburg 1988). In addition, it extended previous adult-focused research by examining the cognitive effects of benzodiazepines in children.…”
Section: Introductionmentioning
confidence: 88%
“…Many anaesthesiologists (e.g. DeJong and Verburg 1988) have noted that drug-induced amnesia could also be beneficial to children having surgery, as it might attenuate the psychological difficulties associated with separation from parents and/or problematic anaesthesia induction.…”
Section: Introductionmentioning
confidence: 99%
“…surgery (e.g., DeJong and Verburg 1988;Kupietzky et al 1996;Playfor et al 2000). Midazolam is a benzodiazepine with a short half-life, making it a good candidate for use in the day surgery setting (Smith et al 1981).…”
mentioning
confidence: 98%